A localized glyco-editing probe for revelation of protein-specific glycan function. (October 2021) - Li, Siqiao; Mao, Anwen; Huo, Fan; Wang, Xiaojian; Guo, Yuna; Liu, Lu; Yan, Chao; Ding, Lin; Ju, Huangxian
Graphical abstract: Abstract: The ability to execute live-cell, localized glyco-editing is of pivotal importance for revolutionizing the field of glycobiology but no effective tool has been developed. We report herein the design of protein-specific glyco-editing probes, operating through localized enzyme decaging (LED), for live-cell editing of carbohydrate units on the protein of interest. The integration of aptamer recognition and molecular cloaking/uncloaking-based glyco-enzyme caging/decaging mechanism ensures the protein-specific editing. Proof-of-concept demonstration has been achieved for mucin 1 (MUC1)-specific terminal galactose/ N -acetylgalactosamine (Gal/GalNAc) editing and sialic acid (Sia) trimming on live cells. A unique advantage of our LED strategy is the modular adaptability for performing cascade localized glyco-editing (CALOGE) manipulation through sequential aptamer docking-erasing-docking processes. Moreover, in vivo MUC1-specific Gal/GalNAc editing has also been realized, which enables the fluorescence visualization of Gal/GalNAc on MUC1 in murine bladder. In particular, specific trimming of MUC1-bound Sia on live cells has demonstrated, for the first time, the ability to directly reveal the significant effects of protein-specific glycoform on intracellular signaling and cell migration. These results suggest the probe as a generically applicable investigation tool for the revelation and manipulation of biological functions in association with protein-specific glycoforms.